Mercury concentrations in muscle, brain and bone of Western Alaskan waterfowl - Rothschild, Roger F.N.; Duffy, Lawrence K. (The Science of the total environment, 2005)
Total mercury (THg), which includes both inorganic (Hg 2+) and methylmercury (MeHg) species, has been reported for seabirds in the North Pacific and Alaska. For the Yup'ik and Aleut people of Alaska, waterfowl are a small but important seasonal component of the diet, but many Alaskan species have not been studied extensively for the presence of mercury. Birds are good subjects for examination of mercury concentrations because they feed at different trophic levels, they can be long-lived, and many are both abundant and widely distributed. In this study, we present the levels of mercury in muscle, brain, and bone tissue of 140 birds taken by subsistence food users across Western Alaska. THg wet weight mean concentrations in the 18 species of waterfowl surveyed ranged from 0.8 to 268.6 ng/g in muscle, from 0.4 to 197.7 ng/g in brain and from 0.7 to 422.9 ng/g in bone. The null hypothesis that there are no interspecific differences in the level of total mercury in the 18 species of Alaska birds surveyed was not supported. We found interspecific differences with the Lesser Scaup ( Aythya affinis), and the Black Scoter ( Melanitta nigra), having the highest muscle tissue levels of THg. In general, THg mean levels were higher in muscle than in brain with the exceptions of the Bar-tailed Godwit and Northern Shoveler. Bone THg were highest in the Black Scoter. The mean values for THg in the species studied are unlikely to cause adverse reproductive or behavioral effects in the birds.